Efforts to Achieve Legal Justice in Social Conflict Resolution in Register 45 Mesuji Lampung - I Ketut Seregig (Faculty of Law, Universitas Jenderal Soedirman, 2019)
This research focuses on efforts to provide solutions in resolving social conflicts that occur between the community and the company PT Silva Inhutani at Register 45 in Mesuji Lampung, which has been running for 14 years (2005-2019), but within that period there has not been a comprehensive settlement. This article is one of the solutions in realizing legal justice so that social conflicts in the Register 45 Mesuji Lampung do not cause futile casualties. We also found that monopolistic practices were carried out by the company in implementing the partnership policy issued by the government and the practice of intimidation by the company using thugs to ban and evict land that was worked on by the community at the Register 45 Mesuji Lampung. Some of the most successful references in resolving social conflicts found by journal authors, they are Pham Huu Ty et al (2013), Rafael Reuveny et al (2007), Franks et al (2014), Ismael Rafols et al (2012), Buijs et al. (2012) 2013), Lambin et al (2001) and Pauline E. Piters (2004), whose research was carried out in countries; Vietnam, Latin America, England and Africa. The approach used in resolving social conflicts is the